Assessing the Efficacy of AI-Driven Corrective Feedback via WhatsApp Application to Improve ESL Learners’ Writing Skills: An Experimental Study - Jamshed, Mohammad; Fatimah Albedah; Mohd Sajid Ansari; Sameena Banu (International Journal of Interactive Mobile Technologies (iJIM), 2025)
Writing in English poses challenges due to the intricacy of its grammatical rules; however, these challenges may be effectively overcome through artificial intelligence (AI)-driven technologies. As there is insufficient research on AI-enabled WhatsApp for English language learning and instruction, this study examines how WhatsApp’s AI system enhances ESL learners’ writing skills. To deal with these gaps, the study aims to assess how AI-driven corrective feedback through the WhatsApp application enhances ESL learners’ writing skills by reducing grammatical errors within the framework of the interactionist theory of second language learning. The present research study utilized a quasi-experimental design involving two groups—an experimental group and a control group—to experiment. The experimental group was subjected to treatment involving AI-driven corrective feedback via WhatsApp application, whereas the control group did not receive such feedback. Data were collected from 112 undergraduate participants in India at two intervals: a pre-test and a post-test. The participants’ written submissions were assessed and scored using ChatGPT 4.0. The method of statistical analysis, repeated measures analysis of variance (RM-ANOVA), was applied to analyze the score. The results of the study showed that ESL learners who received AI-driven corrective feedback via WhatsApp performed better than those who received traditional feedback, particularly in correcting complex grammatical errors related to subject-verb agreement errors, tense errors, pronoun errors, fragment errors run-on sentences, comma splices, misplaced modifiers, apostrophe errors, capitalization errors, word choice errors/lexical errors, and preposition errors in their writing. The study found that augmented feedback systems and AI-driven corrective comments in ESL classrooms could enhance writing skills.